The vulnerabilities of agricultural land and food production to future water scarcity - Fitton, N.; Alexander, P.; Arnell, N.; Bajzelj, B.; Calvin, K.; Doelman, J.; Gerber, J.S.; Havlik, P.; Hasegawa, T.; Herrero, M.; Krisztin, T.; van Meijl, H.; et al. (Global environmental change, 2019)
•We examine risks to current agricultural land to future changes in water availability.•We present a multiple model inter-comparison of future land demand and water availability.•Eleven percent of croplands and ten percent of grasslands are at risk from declining water availability.•Changes in diet and waste reduction offer a buffer against land loss and food insecurity. Rapidly increasing populations coupled with increased food demand requires either an expansion of agricultural land or sufficient production gains from current resources. However, in a changing world, reduced water availability might undermine improvements in crop and grass productivity and may disproportionately affect different parts of the world. Using multi-model studies, the potential trends, risks and uncertainties to land use and land availability that may arise from reductions in water availability are examined here. In addition, the impacts of different policy interventions on pressures from emerging risks are examined. Results indicate that globally, approximately 11% and 10% of current crop- and grass-lands could be vulnerable to reduction in water availability and may lose some productive capacity, with Africa and the Middle East, China, Europe and Asia particularly at risk. While uncertainties remain, reduction in agricultural land area associated with dietary changes (reduction of food waste and decreased meat consumption) offers the greatest buffer against land loss and food insecurity.